Recurrence and chronicity of bonding disorders diagnosed using the structured interview: case report - Yumi Nishikii; Yumi Nishikii; Yoshiko Suetsugu; Hiroshi Yamashita; Keiko Yoshida; Keiko Yoshida (Frontiers in Psychology)
IntroductionAlthough emotional rejection, a core concept of bonding disorders, and pathological anger, which may harm the baby, can coexist, they have different clinical features and require different intervention strategies. Only limited reports have been published on the recurrence and chronicity of emotional rejection. To clarify this, in-depth investigations that utilize structured interviews rather than self-reported questionnaires are required.MethodsThe participant was a 29-year-old woman at the first stage of delivery who had experienced three childbirths with different degrees of bonding disorders. We applied a section named “Mother-infant relationship” within the 6th Stafford interview developed by Brockington, which was used to assess bonding disorders, to report this case systematically. We also used the criteria for disorders of the mother-infant relationship developed alongside the interview.ResultsBonding disorders were diagnosed for this participant, with the first child as “threatened rejection” and the second and third as “mild disorders” (delayed positive feelings). Each improved with treatment within approximately 1 year; however, rejections recurred at different degrees when the next child was born. She was also diagnosed with pathological anger towards her first child, episodes of postpartum depression, and complaints of insomnia after the birth of all three children.ConclusionEmotional rejection, pathological anger towards the baby, and infant-focused anxiety, in this case, should be diagnosed individually and appropriate care should be provided for each. Cases systematically documented using the Stafford Interview should be accumulated to facilitate clinical and research work on bonding disorders.